Meta-Analysis of Flipped Classroom on Students’ Mathematics Abilities: Effectiveness and Heterogeneity Analysis - Endang Sulistyowati; Hukom, Julham; Ali Muhtadi (JTP - Jurnal Teknologi Pendidikan, 2023)
Despite numerous studies investigating whether the Flipped Classroom method is more effective in enhancing students’ mathematical abilities compared to conventional teaching methods, previous research has shown inconsistent results. This study aims to examine the effectiveness of the Flipped Classroom method on students’ mathematical abilities compared to conventional methods and to investigate the factors that can influence the effectiveness of using the Flipped Classroom method on students’ mathematical abilities. The research design used in this study is a meta-analysis, analyzing 42 effect sizes from 31 primary studies that meet inclusion criteria. The results of the analysis, using a random-effects approach, yielded a combined effect size of (g = 1.05; p < 0.01). It can be concluded that the use of the Flipped Classroom method significantly contributes to students’ mathematical abilities and is more effective compared to conventional teaching methods. Furthermore, the analysis of heterogeneity found that the effectiveness of using the flipped classroom method on mathematical abilities is influenced by moderator variables such as the type of measured abilities, platform, type of experimental group, country, and publication type. However, it was not influenced by variables such as educational level and publication year. The findings of this meta-analysis provide more accurate results regarding the inconsistent effect size variations and enrich the knowledge insights about the effectiveness of using the Flipped Classroom method in enhancing students’ mathematical abilities.